EDUCATION AND SCHOOL LIFE IN ENGLAND (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores the structure, features, and values of the education system and school life in England. It presents an overview of the key stages of education, types of schools, the daily routine of students, assessment systems, and school culture. The paper also highlights current challenges in English education and ongoing reforms aimed at improving educational quality and inclusiveness. It is intended for students, teachers, and researchers who are interested in understanding how the British education system operates and what makes it unique in the global context.Annotatsiya: Ushbu maqolada Angliyadagi ta’lim tizimi va maktab hayoti tuzilishi, xususiyatlari hamda asosiy qadriyatlari yoritib beriladi. Unda ta’lim bosqichlari, maktab turlari, o‘quvchilarning kundalik hayoti, baholash tizimi va maktab madaniyati haqida umumiy ma’lumot beriladi. Shuningdek, Angliya ta’lim tizimidagi dolzarb muammolar va ta’lim sifatini yaxshilashga qaratilgan islohotlar ham ko‘rib chiqiladi. Ushbu maqola ingliz ta’lim tizimini chuqurroq o‘rganishni istagan o‘quvchilar, o‘qituvchilar va tadqiqotchilar uchun mo‘ljallangan.